DEVELOPMENT TRENDS OF ISLAMIC FINANCE WORLDWIDE (Conferencea, 2023)
In 2021, Islamic finance grew 17% to nearly US$4 trillion in assets, spanning sectors like Islamic banking, Sukuk, and funds. Islamic banking, 70% of assets, expanded due to support, efficiency, and demand. Net income surged 290%, and digital banks and LIBOR transition responses showed innovation. Sustainability, governance, knowledge, and awareness improved through IFDI, driving growth and innovation.